Home Management of Childhood Asthma Exacerbations - Yeung, Telford Y. (Pulm Ther, 2018)
INTRODUCTION: Effective home management of childhood asthma by caregivers requires education along with a written asthma action plan (AAP), which should outline clear instructions for treatment during exacerbations. However, a large number of asthma exacerbations continue to be managed in the emergency department (ED) and in hospitals, particularly in Canada. The objective of this study was to assess caregiver management of acute asthma at home following the 2015 Global Initiative for Asthma (GINA) guidelines and to identify factors that may be associated with deviations from these guidelines. METHODS: 122 caregivers of children, aged 3–17 years, with physician diagnosed asthma, completed a paper-based questionnaire. Correct caregiver management (defined according to the GINA guidelines) of acute asthma as well as their use of an AAP were assessed. RESULTS: Out of all caregivers, 74.6% incorrectly treated their child’s asthma exacerbation in a home setting. Among those who used an AAP, we observed significantly more ED visits (0.9 ± 1.2 versus 0.5 ± 0.9, p = 0.04) and hospitalizations (0.2 ± 0.4 versus 0.0 ± 0.0, p = 0.02) when compared to non-AAP users in the past 1 year. CONCLUSIONS: Caregivers of children with asthma in Canada may still lack skills for proper home management of asthma exacerbations. We found a higher number of ED visits and hospitalizations in those using an AAP compared to those who did not use an AAP. These data suggest that current AAPs may not be sufficient for home asthma management. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s41030-018-0061-y) contains supplementary material, which is available to authorized users.